The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1080/08946566.2015.1093990
|View full text |Cite
|
Sign up to set email alerts
|

Financial Exploitation of Older Women: A Case Analysis Using the Struggle for Recognition Theory

Abstract: This article aims to make a theoretical contribution to the field of mistreatment of older adults by introducing Honneth's Struggle for Recognition theory in order to document financial mistreatment of older women. Through a case analysis of an older woman financially exploited by her son, considering self-agency and structure, it shows how financial mistreatment disrespects the three components of Honneth's theory, primary relationships, legal relations, and community of value. Personal integrity, social inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Collectively, the identified articles addressed four broad EFFE topics. The most commonly addressed topics were (a) perception/defining of EFFE ( n = 4; Lee & Eaton, 2009; Lee et al, 2012; Lee et al, 2013; Setterlund et al, 2007), (b) risk and protective factors for victims and perpetrators ( n = 7; Bagshaw et al, 2013; Beaulieu et al, 2015; Betz‐Hamilton & Vincenti, 2018; DeLiema, 2018; Knight et al, 2016; Mukherjee, 2013; Zannettino et al, 2015), (c) impacts on family systems ( n = 2; Petrusic et al, 2015; Vincenti et al, 2014), and (d) challenges in reporting EFFE ( n = 2; Adams et al, 2014; Wendt et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Collectively, the identified articles addressed four broad EFFE topics. The most commonly addressed topics were (a) perception/defining of EFFE ( n = 4; Lee & Eaton, 2009; Lee et al, 2012; Lee et al, 2013; Setterlund et al, 2007), (b) risk and protective factors for victims and perpetrators ( n = 7; Bagshaw et al, 2013; Beaulieu et al, 2015; Betz‐Hamilton & Vincenti, 2018; DeLiema, 2018; Knight et al, 2016; Mukherjee, 2013; Zannettino et al, 2015), (c) impacts on family systems ( n = 2; Petrusic et al, 2015; Vincenti et al, 2014), and (d) challenges in reporting EFFE ( n = 2; Adams et al, 2014; Wendt et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The Struggle for Recognition Theory posits that social conflicts between at least two individuals occur as a result of asymmetrical social relations or inequalities, whereas social confrontations are moral patterns of a struggle for recognition. Beaulieu et al (2015) was the only identified EEFE study to apply the Social Recognition Theory lens when introducing a single case analysis of a widow financially exploited by her son. Beaulieu et al (2015) considered self‐agency and social structure, illustrating how financial mistreatment disrespected the close, trusted parent–child relationship; denied the elder victim's legal rights; and threatened the dignity of the elder victim.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Em complemento, como a aposentadoria representa uma fonte de renda para milhares de famílias, o idoso permanece na função de provedor da família, mesmo com filhos adultos, casados e com filhos, residindo ou não na casa dos pais. Esse padrão familiar pode perpetuar até o fim de suas vidas, colocando o idoso, cada vez mais, na situação de ter que distribuir sua aposentadoria ou pensão entre os seus familiares (Adams et al, 2014;Beulieu, Crevier, D´Amours, & Diaz, 2015;Castle et al, 2015;Harries, Davies, Gilhooly, & Tomlinson, 2014;Harries, Yang, Davies, Gilhooly, & Thompson, 2014). Além disso, a vulnerabilidade pode ser maior em casos de isolamento, solidão, perdas recentes de parentes, desemprego na família, deficiência física ou mental, embora não haja um comportamento homogêneo, podendo atingir homens e mulheres de diferentes classes sociais (Irigary, Esteves, Pacheco, Grassi-Oliveira, & Argimon, 2016).…”
Section: Consumo De Crédito E Vulnerabilidades Dos Consumidores Idososunclassified